Physiological harmony of hormones related to the thyroid gland function in cretinous sheep - A-S. U, et.al, Dr. Hassan (Al-Qadisiyah Journal of Pure Science, 2017)
The present study showed that cretinous rams and ewes revealed an obvious elevation of TSH values accompanied with a declined values of both T3 and T4 from the same samples. Each of these results revealed significant differences in probability values under 0.05 (p< 0.05) when compared with samples from normal sheep of the same species. It can be concluded that cretinous sheep had a disturbance in thyroid physiology opened the hypothesis that it is primary hypothyroidism type.